DAKWAH MODERAT DAN PERLAWANAN SOSIAL TERHADAP KOLONIALISME: STUDI KASUS SULTAN MAHMUD BADARUDDIN II - Niswah, Choirun; Fitriyana, Nur; Bety, Bety; Zuhdiyah, Zuhdiyah; Darmayanti, Kusumasari Kartika Hima; Mahmud, Adnan (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2024)
This study analyzes the moderate preaching of Sultan Mahmud Badaruddin II as a social resistance strategy against colonialism, emphasizing inclusive values, tolerance, and respect for diversity. The Sultan’s preaching focused on spiritual aspects, strengthening social solidarity through non-violent approaches, and integrating local cultures. A qualitative historical approach was used to explore the implementation of the Sultan’s preaching in the Palembang Sultanate and during his exile in Ternate. The findings reveal that the Sultan’s moderate preaching became an effective tool in building social harmony and non-violent resistance. The teachings of the Sammaniyah Order disseminated by the Sultan strengthened the local community’s religious identity while creating strong and sustainable cross-cultural solidarity. These findings affirm the relevance of religious moderation as an adaptive instrument for social resistance, both in the context of colonialism and the challenges of diversity in the modern era. In conclusion, the religious moderation practiced by Sultan Mahmud Badaruddin II offers a leadership model capable of fostering social harmony. It is highly relevant for resolving conflicts peacefully in various global contexts